Cloning of an epoxide hydrolase-encoding gene from Aspergillus niger M200, overexpression in E. coli, and modification of activity and enantioselectivity of the enzyme by protein engineering - Kotík, Michael; Štěpánek, Václav; Kyslík, Pavel; Marešová, Helena (Journal of biotechnology, 2007)
The gene encoding an epoxide hydrolase from Aspergillus niger M200 has been cloned and its sequence determined. The gene is interrupted by seven introns, one exon being only nine nucleotides long. The non-coding 5'- and 3'-regions of the mRNA are composed of 47 and 76 nucleotides, respectively. Overexpression of the fungal epoxide hydrolase in E. coli TOP10 has led to a 15-fold increase in specific activity (compared to the wild-type strain). Saturation mutagenesis at codon 217 resulted in the discovery of nine enzyme variants showing in several cases profound differences in activity and enantioselectivity towards various epoxides when compared to the data of the wild-type enzyme. The site 217 is located at the entrance of the tunnel that provides the substrate with access to the active site. The exchange of Ala at this position for Cys has led to a doubled enantioselectivity (E-value of 5.0) towards benzyl glycidyl ether. The same substitution resulted in a threefold-enhanced activity of the enzyme towards allyl glycidyl ether and styrene oxide without affecting enantioselectivity. The variant A217L showed an enhanced enantioselectivity towards tert-butyl glycidyl ether reaching an E-value of 100 (from 60 for the wild-type enzyme). Replacement of A217 by Val has led to higher activity towards allyl glycidyl ether by a factor of six. The substitutions Ala-->Glu and Ala-->Gln increased the enantioselectivity towards allyl glycidyl ether and styrene oxide by over 50% to E-values of 10 and 16, respectively. The study underlines that single amino acid exchanges in the substrate tunnel region can lead to significant improvements in enantioselectivity and activity of the epoxide hydrolase from A. niger M200.
Keywords: geny hub; Aspergillus niger; Recombinant Proteins; sekvence nukleotidů; DNA, Fungal; proteinové inženýrství; Kinetics; fylogeneze; biotechnologie; Cloning, Molecular; Epoxide Hydrolases; Phylogeny; klonování DNA; komplementární DNA; epoxid hydrolasy; mutageneze cílená; Escherichia coli; Protein Engineering; Amino Acid Substitution; DNA fungální; molekulární modely; rekombinantní proteiny; Models, Molecular; Mutagenesis, Site-Directed; substrátová specifita; kinetika; stereoizomerie; Genes, Fungal; Catalytic Domain; Biotechnology; Substrate Specificity; substituce aminokyselin; Financing, Organized; Base Sequence; DNA, Complementary; financování organizované; katalytická doména; Stereoisomerism